The Influence of Job Training, Work Discipline and Work Motivation on the Performance of Global Prima Medan Foundation Employees - Hutabarat, Elvy Noveliany; Nazmi, Hendra; Napitupulu, Eunike; Winata, Chelsie Hanny; Amrani, Amrani (International Journal Of Economics Social And Technology (IJEST), 2024)
This research was conducted with the aim of finding out how much influence Job Training, Discipline and Motivation has on Global Prima Foundation Employee Performance, because Employee Performance is one of the things that must be achieved at the top level. Both individually and simultaneously, this research was also carried out to find out which one has a more dominant influence on employee performance. The population of the research was carried out by Global Prima Foundation Medan employees with a minimum sample size of 86 respondents using quantitative and technical digital analysis methods, namely large-scale linear analysis. The results of the research show that work training has no significant positive effect on employee performance, work discipline has a significant positive effect on employee performance, work motivation has a significant positive effect on employee performance, but as a result of simultaneous work training, work discipline, motivation has a significant positive effect on employee performance.